Climate Change Contribution to the Emergence or Re-Emergence of Parasitic Diseases. (25th September 2017) - Short, Erica E; Caminade, Cyril; Thomas, Bolaji N
The connection between our environment and parasitic diseases may not always be straightforward, but it exists nonetheless. This article highlights how climate as a component of our environment, or more specifically climate change, has the capability to drive parasitic disease incidence and prevalence worldwide. There are both direct and indirect implications of climate change on the scope and distribution of parasitic organisms and their associated vectors and host species. We aim to encompass a large body of literature to demonstrate how a changing climate will perpetuate, or perhaps exacerbate, public health issues and economic stagnation due to parasitic diseases. The diseases examined include those caused by ingested protozoa and soil helminths, malaria, lymphatic filariasis, Chagas disease, human African trypanosomiasis, leishmaniasis, babesiosis, schistosomiasis, and echinococcus, as well as parasites affecting livestock. It is our goal to impress on the scientific community the magnitude a changing climate can have on public health in relation to parasitic disease burden. Once impending climate changes are now upon us, and as we see these events unfold, it is critical to create management plans that will protect the health and quality of life of the people living in the communities that will be significantly affected.